Effects of operating conditions on the morphology and internal structure of soot particles emitted from an agricultural tractor. (October 2020) - Liu, Xueyuan; Liu, Jinqu; Zhao, Longqing; Ma, Zhilei; Li, Jiaqiang; Wang, Xiao; Chen, Wengang; He, Chao
Abstract : Tractors are widely used in agricultural production as the main agricultural power machinery. Hence, in terms of understanding the airborne emissions produced by agriculture, it is important to study the microscopic characteristics of soot particulate matter in tractor exhaust. The morphology and internal structure of soot particles emitted from an agricultural tractor under different operating conditions were examined using transmission electron microscope (TEM) and were then analysed by digital image processing technology. The results revealed a close relationship between the working conditions of tractor and the morphology and structure of soot particles produced. Firstly, the fringe length of soot particles was between 0.2 and 3 nm and its mean fluctuated between 0.5 and 0.9 nm secondly the fringe tortuosity was between 1 and 1.6, and its mean fluctuated between 1.11 and 1.15. Finally the fringe separation was mainly distributed between 0.28 and 0.52 nm, and its mean fluctuated between 0.39 and 0.41 nm. Changes in the tractor operating conditions (e.g. idling, moving, carrying out rotary tillage, and ploughing) showed that as the engine load increased, the fringe length increased, the tortuosity and separation of the fringes decreased, the arrangement of fringes became more regular, the degree of graphitisation increases, oxidation activity decreased, and the soot particles became more stable. This work contributes to research into the mechanism of the formation of particulate matter, and is also beneficial for assessing environmental impacts from the detailed morphological characteristics of soot particles. Highlights: Exhaust sampling of a tractor engine in practical working conditions was collected. Morphology of particulate matters from agricultural tractor were measured in TEM. Fringe parameters of particle were analysed by digital image processing technology. Relationships working conditions and characteristics of particle were revealed.